1996
DOI: 10.1152/ajpcell.1996.271.4.c1303
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of amiloride-sensitive, Na(+)-conducting ion channels in the kidney

Abstract: Amiloride-sensitive, electrogenic Na+ absorption across the distal nephron plays a vital role in regulating extracellular fluid volume and blood pressure. Recently, two amiloride-sensitive, Na(+)-conducting ion channel cDNAs were cloned. One, an epithelial Na(+)-selective channel (ENaC), is responsible for Na+ absorption throughout the distal nephron. The second, a guanosine 3',5'-cyclic monophosphate (cGMP)-inhibitable cation channel, is conductive to Na+ and Ca2+ and contributes to Na+ absorption across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The initial characterization of wild-type ␣-ENaC expressed in CHO cells demonstrated that channels with properties similar to those seen in other expression systems and endogenous tissues could be expressed (6,14). Another interesting observation was that the P o of the channels fell into two distinct groups.…”
Section: Differences In Open Probability and Mean Open Timesmentioning
confidence: 84%
See 1 more Smart Citation
“…The initial characterization of wild-type ␣-ENaC expressed in CHO cells demonstrated that channels with properties similar to those seen in other expression systems and endogenous tissues could be expressed (6,14). Another interesting observation was that the P o of the channels fell into two distinct groups.…”
Section: Differences In Open Probability and Mean Open Timesmentioning
confidence: 84%
“…However, regardless of which channel type is expressed, one of the defining characteristics of all these channels is their block by the diuretic amiloride, a substituted pyrazinoylguanidine. The tertiary structure of all the subunits is similar: each subunit is predicted to span the membrane twice, to have a large extracellular loop, and to have short intracellular NH 2 and COOH termini (2,6). Because amiloride blocks the channel from the extracellular surface of the channel protein, it is possible that one or more of the extracellular loops could play a role in amiloride's interaction with and block of the channel by stabilizing amiloride in the channel pore.…”
mentioning
confidence: 99%
“…ENaC subunits are coexpressed in the distal renal tubule and collecting ducts (5,6). A role for ENaC in electrolyte and fluid balance is deduced from mutations of ENaC subunits that cause two diseases: pseudohypoaldosteroidism (PHA, Type 1) and Liddle's syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned proteins have been localized to the distal nephron of rabbit (1,9,15,16,26,29,37) and rat (4, 5, 10, 22, 33-35, 39, 41) but only in part in mice [e.g., NKCC2 (32), NCC (23), ENaC (6,27), and CB (38)]. Previous studies revealed significant differences in the distribution patterns of salt and water transport proteins along the distal nephron between rabbits (1, 26) and rats (24,33,41).…”
mentioning
confidence: 99%